EFEKTIVITAS PEMBELAJARAN BERDIFERENSIASI DENGAN MODEL TUTOR TUTEE SEBAYA UNTUK MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA SISWA DI MASA PANDEMI COVID-19 - Yunita Yunita (Universitas Tribhuwana Tunggadewi, 2022)
This study aims to determine the effectiveness of applying the peer tee tutor learning model to increase students' motivation to learn mathematics during the Covid-19 pandemic. This study used an observation method where observation of the learning process was carried out on 33 students in class XI IPS SMK Negeri 6 Malang. The results found that there were 19 students who had a visual learning style, (57.6%). There were 7 students out of 33 students who had auditoria learning styles (21.21%) and 7 other students. The application of differentiated learning with the tutee tutor model turns out to be effective to use because it can overcome the decline in student learning motivation.This is due to its superiority that is able to embrace all the diversity of different student learning characteristics by meeting all student needs based on their abilities and paying attention to student learning readiness so that it can bring out the learning motivation of each student in the class by applying ethical dilemma analysis with 4 paradigms, 3 decision-making principles and 9 decision-making steps.